19 Barrett's oesophagus in childhood: a population-based case series analysis. (5th April 2017) - Twohig-Bennett, L; Coleman, HG; Murray, LJ; McManus, DT; Gavin, AT; Bhat, S; Johnston, BT
Abstract : Background: Adults detected with Barrett's oesophagus (BO) are often entered into surveillance for oesophageal adenocarcinoma (OAC), although cancer risk is relatively low. More rarely, BO can be detected in children. Little is known about the epidemiology of paediatric BO, and it is unclear what the optimal surveillance regimes are in these children. Aim: To evaluate the demographic and clinical characteristics, and future neoplastic progression risk in all paediatric BO patients diagnosed in Northern Ireland between 1993 and 2010. Method: Data was collected using the Northern Ireland BO register and matched to the Northern Ireland Cancer Registry for OAC outcomes until end 2013. Age-adjusted incidence of paediatric BO was calculated, and chi-squared tests performed to compare characteristics between paediatric and adult BO patients. Results: Over 18 years, 42 paediatric BO patients were identified, equivalent to an age-adjusted incidence of <2 per 1 00 000 children. No clear age distribution was evident, with cases ranging from newborns to 15 years old. 85.7% of patients were male, which was a significantly higher male:female ratio than adult BO patients (p<0.001). No patients progressed to HGD/OAC, although the eldest patient would be aged 34 years by the end of follow-up. Conclusions: This is the largest series of paediatric BO ever to be reported. It demonstrates that paediatric BO is a rare disease. The male preponderance of this condition is even more apparent in childhood compared with adult cases. No children developed HGD/OAC during follow-up, suggesting that regular surveillance is not required, at least until early adulthood.